2020
DOI: 10.1177/0040517519900384
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of soft armor: the response of single-ply para-aramid and ultra-high molecular weight polyethylene fabrics under ballistic impact

Abstract: Typical soft armor systems are constructed of multiple layers of a single fabric type. This empirical research sought to begin optimization of these systems through hybridization, sequencing dissimilar armor fabrics to maximize their ballistic protective performance, by first investigating single plies with a spectrum of properties to determine their behavior and response to impact. Eight individual plain weave fabrics with varying yarns and thread counts were manufactured from para-aramid and ultra-high molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Results of the ANOVA are listed in appendix Table A4. Also, the values of F for all velocities are much greater than the critical value of F (3,16) corresponding to a ¼ 0.05, indicating that the performance of different samples are not statistically similar. It can be seen in Figure 10 that Panels 2 and 4 show a similar performance, which is outperformed by that of Panels 1 and 3.…”
Section: Impact Testsmentioning
confidence: 87%
See 2 more Smart Citations
“…Results of the ANOVA are listed in appendix Table A4. Also, the values of F for all velocities are much greater than the critical value of F (3,16) corresponding to a ¼ 0.05, indicating that the performance of different samples are not statistically similar. It can be seen in Figure 10 that Panels 2 and 4 show a similar performance, which is outperformed by that of Panels 1 and 3.…”
Section: Impact Testsmentioning
confidence: 87%
“…The impact results are subjected to analysis of variance (ANOVA), which is shown in appendix Tables A1-A3. It has been found that the values of F for all the velocities are much greater than the critical value of F (3,16) corresponding to a ¼ 0.05, which is 5.29 (the F value is the ratio of the mean squares; it is an estimate of population variance that accounts for the degree of freedom used to calculate that estimate). We are 99% confident (1-a) that the depths of the BFS are not statistically equal for Samples 1-4.…”
Section: Impact Testsmentioning
confidence: 96%
See 1 more Smart Citation
“…Body armours for ballistic protection are constructed using cross-ply laminates of ultra-high molecular weight polyethylene (UHMWPE) and para-aramid filaments. 1,2 Laminated composites of UHMWPE filaments and linear low density polyethylene (LDPE) film with cross-ply pattern exhibit higher ballistic protection than woven structure based architecture. 3,4 Laminates show the highest impact resistance against small calibration projectiles such as hemispherical, fragments and spheres.…”
Section: Introductionmentioning
confidence: 99%
“…This study sought to advance previous research on single yarns and plies 24 to generate further understanding of fabric response when combined in a multi-ply system. With limited empirical work available on hybrid systems, where studies have focused more on solely hybrid fiber systems, this research investigated the response of both homogenous and hybrid multi-ply fabrics that varied by fiber type and weave parameters.…”
mentioning
confidence: 99%